A tutorial on solid-phase analytical derivatization in sample preparation applications - Azamat Temerdashev; Sanka N. Atapattu; Yu-Qi Feng (Journal of Chromatography Open)
Solid-phase analytical derivatization is a versatile sample preparation technique that enhances analysis accuracy, efficiency, reproducibility, and sensitivity. The technique combines the advantages of analytical derivatization and solid-phase extraction, providing a versatile approach for analysing analytes with various functional groups in complex matrices. Analytical derivatization is a technique used for functional group analysis that involves modifying the structure of an analyte to enhance sensitivity and specificity. Solid-phase analytical derivatization is a one-pot procedure that combines analytical derivatization and extraction. In the presence of acids, it can derivatize phenols, carboxylic acids, and other analytes. Furthermore, solid-phase analytical derivatization increases the reaction rate of carbonyl compounds, making it easier to extract aldehydes and ketones rapidly. This technique utilises electrophoresis, chromophores, fluorophores, and functional groups for detection and extraction. It initially began as a batch procedure but has now developed into an automated, microextraction, and derivatization method. Solid-phase analytical derivatization is highly efficient due to the significant excess of the derivatizing reagent relative to the analyte, along with the pre-impregnation of derivatizing reagents, which can speed up the process compared to traditional solution-based derivatization. This tutorial aims to provide detailed insights into the practical aspects of implementing solid-phase analytical derivatization in analytical method development and discuss the prospects and future trends.